Balancing social acceptability with treatment effectiveness of an intrusive procedure: a case report. - Grace, N C (1994)
The debate over social acceptability of intrusive procedures has led some school districts to adopt policies allowing punishment for only the most extreme forms of destructive behavior. We investigated the effectiveness of selectively implementing punishment for only the most severe topographies of aggression and property destruction, while less extreme behaviors were ignored. Results indicated that severe behaviors were reduced to near-zero levels only when both severe and less severe behaviors were similarly punished.